Pengaruh Motivasi Belajar Terhadap Karakter Peserta Didik di Fase F - Sari, Mesi Indah; Adison, Joni; Usman, Citra Imelda (Program Studi Bimbingan dan Konseling Islam, 2024)
The existence of students who are less concerned and indifferent to the learning process, as well as the fact that many still struggle to submit assignments on time, motivates this research. The purpose of this study is to analyze the effect of learning motivation on student character in phase F at SMA Negeri 1 Luhak Nan Duo, West Pasaman Regency. This research falls under the category of quantitative descriptive. The study's population consisted of 333 students. 333 students. The study employed a proportional random sampling technique, selecting 77 students from the totThe questionnaire employed the simple linear regression analysis technique as its instrument. sis technique. The study's results indicate that student learning motivation is significantly high. The student's character falls into the very good category. It is also known that there is a significant influence of learning motivation on student character in Phase F of SMA Negeri 1 Luhak Nan Duo. Therefore, we can conclude that the hypothesis, which posits a strong influence of learning motivation on student character, stands at 83.5%. This study contributes to a deeper understanding of the importance of learning motivation in shaping student character.